Evaluasi Pemanfaatan Aplikasi Game dalam Ujian Bahasa Indonesia (Studi Kasus di SMAN 1 Polanharjo Klaten) - Yanuar Bagas Arwansyah; Nina Queena Hadi Putri; Ryan Hidayat; Khusnul Khotimah; Sarwiji Suwandi (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
This study aims to evaluate the implementation of the exam by utilizing game applications in Indonesian subjects at SMA Negeri 1 Polanharjo. This study involved a teacher and four students, consisting of two students in class X and two in class XI. This research uses a qualitative approach with a case study strategy; research data is obtained by observation and interviews; data validity is done by triangulation of data and sources. The results of the research: (1) the implementation of the Indonesian language exam at SMA Negeri 1 Polanharjo has used the Scorative game application as a learning evaluation tool; (2) the advantages of using Scorative games in exams, namely making students more enthusiastic in carrying out exams and making the exam atmosphere more fun; (3) deficiencies in the use of Scorative games, namely that they cannot be used for large-scale examinations due to limited facilities and infrastructure as well as the competence of human resources in the use of technology; and (4) obstacles that arise in the implementation of game-based exams, namely the readiness factor for the quality and quantity of devices, networks, and the level of students' understanding of the use of applications.